1995
DOI: 10.1177/030089169508100604
|View full text |Cite
|
Sign up to set email alerts
|

Bone Marrow Biopsy for the Staging of Non-Hodgkin's Lymphoma: Bilateral or Unilateral Trephine Biopsy?

Abstract: On the basis of these results and of the present therapeutic strategies, we propose: bilateral bone marrow biopsy for clinical stages I-II of all NHL; no bone marrow biopsy at disease onset for clinical stages III and IV of A to H histologic subtypes of the WF; unilateral bone marrow biopsy (A-C subtypes of the WF) or bilateral (D-H of the WF), after the regression of extramedullary localizations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 8 publications
0
12
0
Order By: Relevance
“…This is supported by the improved sensitivity of bilateral over unilateral BMB. 22 Furthermore, dilution of the aspirate samples with peripheral blood during the procedure may decrease the proportion of neoplastic cells to below the threshold of detection by FC.…”
Section: Discussionmentioning
confidence: 99%
“…This is supported by the improved sensitivity of bilateral over unilateral BMB. 22 Furthermore, dilution of the aspirate samples with peripheral blood during the procedure may decrease the proportion of neoplastic cells to below the threshold of detection by FC.…”
Section: Discussionmentioning
confidence: 99%
“…The trephine biopsy specimen should be at least 2 cm and mostly comprised of trabecular bone (70). Bilateral bone marrow samples should be obtained if possible, since many studies have indicated a high higher incidence of detection than with unilateral specimens (74)(75)(76)(77)(78)(79). A bone marrow aspirate and biopsy touch imprint should be obtained if possible, since these specimens may preempt the biopsy findings and guide the use of special studies such as flow cytometry and fluorescence-in-situ hybridization (80).…”
Section: Nonhematopoietic Tumorsmentioning
confidence: 99%
“…Despite conflicting evidence to support its efficacy as an ancillary tool in initial diagnosis and staging [11,[16][17][18][19][20], FC is frequently requested concurrent with LM examination of tissue or cellular morphology. It is well established that increasing the number of specimens submitted for morphologic assessment increases sensitivity of detection of malignant diseases [21][22][23][24].…”
Section: Discussionmentioning
confidence: 99%